Phosphatidylserine functions as the major precursor of phosphatidylethanolamine in cultured BHK-21 cells. - Voelker, D R (1984)
Pulse-chase experiments with [3H]serine provide evidence that significant amounts of phosphatidylserine turn over to form phosphatidylethanolamine in mammalian cells in tissue culture. Phospholipase C hydrolysis of [3H]phosphatidylethanolamine synthesized from [3H]serine by baby hamster kidney (BHK-21) cells demonstrates that nearly all of the radiolabel remains in the ethanolamine moiety. Uniform labeling experiments with [3H]serine further demonstrate that the distribution of radiolabel in phosphatidylserine and phosphatidylethanolamine is nearly identical to the mass ratio of these lipids. Physiological concentrations of ethanolamine (20 microM) have only a marginal effect upon the ability of cells in culture to incorporate radiolabeled serine into either phosphatidylserine or phosphatidylethanolamine. These data provide compelling evidence that phosphatidylethanolamine synthesis via phosphatidylserine and phosphatidylserine decarboxylase contributes significantly to membrane biogenesis in mammalian cells.